2022
DOI: 10.3390/ph15070836
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Regulates PPARγ-Dependent Vesicle Formation as well as Cell Death in A549 Human Lung Cancer Cells

Abstract: Extracts of phytocannabinoids from Cannabis sativa have been studied for therapeutic purposes. Although nonpsychoactive CBD has been studied as a promising anticancer drug because it induces apoptosis in many cancer cells, it is also known to induce several physiological changes. In this study, we clarify the functional role it plays in the morphological characteristics of intracellular vesicle formation as well as apoptosis in A549 human lung cancer cells. CBD treatment shows growth inhibition at concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
(45 reference statements)
2
1
0
Order By: Relevance
“…To determine this, we first investigated whether CBD has any particular effects on NSCLC cell lines with diverse genetic backgrounds such as A549 cells (KRAS mutation, P53 wide-type), NCI-H2228 (EML4-ALK variant 3, P53 Q331 * mutation) and HCC-827 (EGFR exon19 deletion mutant, inactivation P53 mutation). A study concluded that CBD treatment regulates several types of cell death via upregulating apoptosis-related proteins, such as p53 in A549 (45). Similarly, our analysis revealed that A549 cells were more sensitive to CBD treatment compared to other cell types, presumably attributable to their p53 wild-type state.…”
Section: Discussionsupporting
confidence: 68%
“…To determine this, we first investigated whether CBD has any particular effects on NSCLC cell lines with diverse genetic backgrounds such as A549 cells (KRAS mutation, P53 wide-type), NCI-H2228 (EML4-ALK variant 3, P53 Q331 * mutation) and HCC-827 (EGFR exon19 deletion mutant, inactivation P53 mutation). A study concluded that CBD treatment regulates several types of cell death via upregulating apoptosis-related proteins, such as p53 in A549 (45). Similarly, our analysis revealed that A549 cells were more sensitive to CBD treatment compared to other cell types, presumably attributable to their p53 wild-type state.…”
Section: Discussionsupporting
confidence: 68%
“…To determine this, we first investigated whether CBD has any particular effects on NSCLC cell lines with diverse genetic backgrounds such as A549 cells (KRAS mutation, P53 wide-type), NCI-H2228 (EML4-ALK variant 3, P53 Q331* mutation) and HCC-827 (EGFR exon19 deletion mutant, inactivation P53 mutation). A study concluded that CBD treatment regulates several types of cell death via upregulation apoptosis-related proteins, such as p53 in A549 [31]. Similarly, our analysis revealed that A549 cells were more sensitive to CBD treatment compared to other cell types, presumably attributable to their p53 wild-type state.…”
Section: Discussionsupporting
confidence: 67%
“…Cannabinoids can interact with their receptors or proteins via cellular pathways, thus affecting the development/progression of diseases, including cancer [35]. Our previous study suggested that CBD shows anticancer activity by inducing PPAR-γ-dependent cytoplasmic vesicles in human lung cancer cells and colorectal cancer cells [36,37]. This biological activity was also observed in colorectal cancer cells, indicating the anticancer effects of cannabinoids on various cancer types.…”
Section: Discussionmentioning
confidence: 90%